Serviço de atividades educativas do Museu Paulista: o estabelecimento de uma área dentro de uma instituição centenária - Souza, Ingrid Ribeiro (2017)
The understanding of museums as educational spaces is relatively new insight in the history of these institutions. Not until the second half of the twentieth century have museums been recognized formally as intrinsically educational institutions. Dialoguing with this question and thinking about the educational role of museums that this research has the proposal to investigate the formation and consolidation of the Educational Activity Service (EAS) of the Paulista Museum, a century-old institution inaugurated in 1895 as a Natural History museum and that today is configured as Museum of History and Material Culture. Thus, the objective in this dissertation is to elucidate the action proposed by EAS to the academic audience, which is the largest audience visiting the Museum. Although the museum has been closed since 2013 due to a renovation, educational activities have not ceased to happen. It is intended, that way, to contribute, integrating the produced theoretical knowledge, that deals with education in museums, with the proposed and presented practice by the Educational Activity Service of the Paulista Museum in these years of work.